Influence of dietary supplementation of Garden cress (Lepidium sativum L.) on liver histopathology and serum biochemistry in rats fed high cholesterol diet (Journal of Advanced Veterinary and Animal Research, 2014)
The objective of current study was to evaluate the effects of Lepidium sativum (LS) on liver histopathology and serum biochemistry in rats fed with high cholesterol diet. A total of 32 rats were divided into four equal groups. The rats of first group (control group) were fed with basal diet, whereas the rats of second group were fed with basal diet mixed with cholesterol (1%). The rats of third and fourth groups were fed with high cholesterol (1%) diet mixed with Lepidium sativum powder at 3 g and 6 g/kg diet, respectively. Total cholesterol, triacylglycerol and alanine transaminase (ALT) activity were increased significantly in the rats fed with high cholesterol diet as compared to control group. LS reduced total cholesterol and ALT; however, higher dose (6 g/kg diet) was found better than lower dose (3 g/kg diet) in reducing serum triacylglycerol. Histopathological findings revealed that liver of cholesterol-treated rats showed varying degrees of vacuolar degeneration, fatty changes, fatty cysts, and lobular disarray. Livers of the LS-treated rats revealed mild to moderate degree of recovery. Conclusively, high dose of LS is recommended as hypocholesterolemic and hypolipidemic agent in rats. http://dx.doi.org/10.5455/javar.2014.a41